A multi-analytical study on the photochemical degradation of synthetic organic pigments. (December 2015) - Ghelardi, Elisa; Degano, Ilaria; Colombini, Maria Perla; Mazurek, Joy; Schilling, Michael; Khanjian, Herant; Learner, Tom
Abstract: This paper summarizes the results of a photochemical ageing study on selected synthetic organic pigments used in paint formulations both as artists' and industrial materials. Some of them are rated by the American Society for Testing and Materials (ASTM) as fugitive. We performed an accelerated ageing test for the first time on the neat pigment powders, without any binder, to determine the lightfastness of the pure pigments. Several techniques were used to compare the aged and un-aged pigments: colorimetric measurements, Fourier transform infrared spectroscopy (FTIR), and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). Colorimetry highlighted a relevant change in colour (ΔE* > 1) after the ageing treatment, whereas Fourier transform infrared spectroscopy technique allowed us to identify specific differences in absorption. Pyrolysis-gas chromatography/mass spectrometry showed different pyrolysis products in the aged pigments, with respect to the un-aged ones. Graphical abstract: Highlights: We present a survey on the lightfastness properties of several synthetic pigments. Colorimetric measurements attested a change in colour (ΔE* > 1) after the ageing. FTIR-ATR suggested the occurrence of oxidation reactions. Py-GC/MS highlighted the breaking of the molecular structure of the pigments.